Statin Use Reduces Decline in Lung Function: VA Normative Aging Study - Alexeeff, Stacey E; Litonjua, Augusto A; Sparrow, David; Vokonas, Pantel S; Schwartz, Joel (American journal of respiratory and critical care medicine, 2007)
Decreased lung function has been linked to increased inflammation and oxidative stress. Statins have demonstrated antiinflammatory and antioxidant properties. We investigated the effect of statin use on decline in lung function in the elderly, and whether smoking modified this effect. Our study population included 2,136 measurements on 803 elderly men from the Normative Aging Study whose lung function (FVC and FEV(1)) was measured two to four times between 1995 and 2005. Subjects indicated statin use and smoking history at each visit. We used mixed linear models to estimate the effects of each covariate, adjusting for subject and possible confounders. For those not using statins, the estimated decline in FEV(1) was 23.9 ml/year (95% confidence interval [CI], -27.8 to -20.1 ml/yr), whereas those taking statins had an estimated 10.9-ml/year decline in FEV(1) (95% CI, -16.9 to -5.0 ml/yr). We also examined the effect of statins with smoking by dividing the cohort into four groups: never-smokers, longtime quitters (quit >or= 10 yr ago), recent quitters (quit < 10 yr ago), and current smokers. We found a significant three-way interaction between time since first visit, statin use, and smoking status (P < 0.001). Within each smoking category, the effect of statins was always estimated to be beneficial, but the size of the improvement in the decline rate varied among smoking groups. We found similar results for FVC decline. Our results indicate that statin use attenuates decline in lung function in the elderly, with the size of the beneficial effect modified by smoking status.